Reproductive form and function in trait-based plant ecology: from species to communities - Csercsáné Vojtkó, Anna (Jihočeská univerzita, 2022)
This thesis focuses on reproductive functional trait patterns across different spatial scales. The following sections document novel results and their relevance in modern plant functional ecological theory. The thesis evaluates evolutionary and environmental processes driving functional trait variability with a special focus on sexual and vegetative reproduction. First, the thesis provides a synthesis on the role of sexual reproductive functional traits in plant community assembly processes pointing to current knowledge gaps (Chapter I). Then, using publicly available databases as well as data from field measurements, the following sections aim at filling these knowledge gaps. On the species level, sexual reproductive traits are identified as one of the most important axes of variability in plant form and function (Chapter II). On the level of communities, functional and phylogenetic diversity is studied within and across different habitat types (Chapter III and IV).
Reproductive form and function in trait-based plant ecology: from species to communities
Keywords: plant community assembly; functional diversity; phylogenetic diversity; plant economic spectrum; floral traits; clonal traits; plant community assembly; functional diversity; phylogenetic diversity; plant economic spectrum; floral traits; clonal traits